Development of a guided internet-based psychological intervention for patients with ischemic heart disease and comorbid anxiety and/or depression: A patient and public involvement study - Robert Ahm; Nina Rottmann; Søren Jensen Skovbakke; Charlotte Helmark; Christina Antoinetta Vasilescu; Susanne S. Pedersen (Internet Interventions, 2025)
Introduction: Ischemic heart disease (IHD) is a leading cause of mortality that is very often accompanied by comorbid anxiety and depression. The aim of this study was to develop MY-CHOICE, a guided internet-based psychological intervention for the treatment of anxiety and depression in IHD patients using patient and public involvement (PPI). Method: We used the framework recommended by the Medical Research Counsel for developing and evaluating complex interventions to develop MY-CHOICE. Patient representatives with IHD and comorbid anxiety and/or depression (n = 5) were recruited from Odense University Hospital and invited to a series of workshops to gather their feedback on the MY-CHOICE prototype. The workshops used the MUST method for the planning, facilitation, data generation and analysis. The MoSCoW principles were used to help the patient representatives in prioritizing among their suggestions. Data were collected by means of audio recordings and observational notes. Results: This study revealed the need for new treatment modules, including how to manage chronic pain and how to navigate the healthcare system. The patient representatives emphasized the importance of shared decision-making in customizing treatment to individual preferences and needs. Discussion: MY-CHOICE represents a patient focused approach to improving mental health in patients with IHD. By integrating patient feedback through PPI, MY-CHOICE aims to deliver tailored psychological treatment, possibly increasing relevance and adherence. Conclusion: This study highlights the necessity of addressing comprehensive needs in IHD patients, including chronic pain, and emphasizes the importance of using shared decision-making to optimize patient engagement and adherence to treatment.